1994
DOI: 10.1029/93wr02401
|View full text |Cite
|
Sign up to set email alerts
|

Field measurement of radial solute transport in fractured rock

Abstract: The results of a tracer experiment conducted in a single fracture are interpreted using a semianalytical model which accounts for advective dispersion, matrix diffusion, mixing in the test zones, and for tortuosity. The experiment was conducted using a conservative tracer which was injected into a steady divergent flow field. Arrival of tracer was monitored in an array of 13 boreholes intersecting the fracture over a square area of approximately 30 rn on a side. The arrival of tracer was detected in 11 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Numerical models and analytical solutions presenting analyses of the effect of matrix diffusion during transport in fractured geologic media have been reported by Neretnieks (1980), 1981), Tang et al (1981), Noorishad and Mehran (1982), Huyakorn et al (1983a and b), Feenstra , Grisak and Pickens (1981), Neretnieks et al (1982), Moreno et al (1985), , ; and for field tracer tests by Jones et al (1992), Novakowski and Lapcevic (1994), IT (1998), , and.…”
Section: Role Of Matrix Diffusion In Contaminant Transportmentioning
confidence: 99%
“…Numerical models and analytical solutions presenting analyses of the effect of matrix diffusion during transport in fractured geologic media have been reported by Neretnieks (1980), 1981), Tang et al (1981), Noorishad and Mehran (1982), Huyakorn et al (1983a and b), Feenstra , Grisak and Pickens (1981), Neretnieks et al (1982), Moreno et al (1985), , ; and for field tracer tests by Jones et al (1992), Novakowski and Lapcevic (1994), IT (1998), , and.…”
Section: Role Of Matrix Diffusion In Contaminant Transportmentioning
confidence: 99%
“…In addition, in some of the tests, the bacteriophage and microsphere were injected simultaneously or separately with chemical tracers to separate the effects of matrix diffusion from advection and dispersion [Champ and Schroeter, 1988;Bales et al, 1989;McKay et al, 1993b;Becker et al, 1999;Reimus and Haga, 19991. At some geologic sites, tracer tests were conducted at different scales to investigate scale effects of transport parameters [Novakowski and Lapcevic, 1994;Frost et al, 1995;Himmelsbach et al, 1998;Jardine et al, 1999;Maloszewski et al, 1999;Baurnle, 20031. Most of all the field tracer tests have been analyzed using analytic or numerical models considering matrix diffusion [e.g., Brettmann et al, 19931, and their reported values of field-scale matrix diffusion coefficients were again used as entries to our data set.…”
Section: Field Tracer Tests and Observationsmentioning
confidence: 99%
“…Tracer tests have long been used to evaluate the crosshole connectivity in fractured rock (Chen 1986;Novakowski and Lapcevic 1994;Sharifi Haddad et al 2015); however, the test results have not shown the exact location of the tracer inlet in the observation well. Nanoscale zero-valent iron (nZVI) has been widely applied to in-situ remediation of groundwater contamination (Wang and Zhang 1997;Varanasi et al 2007).…”
Section: Introductionmentioning
confidence: 99%